Determination of trace metals in hair samples of Iraqis people living in suburban and urban in Basrah governate ,southern of Iraq - Abdullah Y. Khudhair (University of Thi-Qar Journal of Science, 2019)
This study was carried out on human hair samples that were collected from different areas of Basrah Governorate in the year 2009, (67 people of both genders). In the year 2010 (17 people of both genders. The two groups were divided into seven subgroups according to their age. Hair was analyzed for Na, K, Ca, Mg, , Hg, Pb, Cd ,U, Co Cu, As, Fe, Al and Zn; using ICP/Ms instrumentation at maxxam analytical INC , Canada. The results showed levels of most essential and heavy metals that were tested in the year 2009,and the metals tested in the year 2010 were higher than international levels. A significant difference have been observed P< 0.05 between the same group according to the age criteria. Significant differences were observed in between subgroups of the year 2009 Vs. 2010. The maximum reading of Hg, Pb, U, Cu, Ca, Mg, As and Co was found in subgroup (2), Fe and Zn in subgroups 4, 5 and 6 respectively for 2009. Samples from 2010,showed the maximum reading of Hg, Pb, Cd, Cu, Zn, Ca, and Co found in subgroup(3), whereas Fe, Mg, Al, and As, levels were high levels in subgroups 1,2 and 4. The high level of heavy metals seen in this study, reveals that these areas where samples were collected from are highly contaminated with these toxic and polluted materials. This high level needs intensive care from the government to protect the environment from these toxic and carcinogenic substances. Also, the existence of Uranium in the samples that were analysis need special care from decision makers due to the potential harm that could be caused by these metals to public welfare.Key words:Toxic elements, heavy metals, Uranium, essential elements .hair sample.